2011
DOI: 10.1112/jtopol/jtq041
|View full text |Cite
|
Sign up to set email alerts
|

Monodromy substitutions and rational blowdowns

Abstract: We introduce several new families of relations in the mapping class groups of planar surfaces, each equating two products of right-handed Dehn twists. The interest of these relations lies in their geometric interpretation in terms of rational blowdowns of 4-manifolds, specifically via monodromy substitution in Lefschetz fibrations. The simplest example is the lantern relation, already shown by the first author and Gurtas ('Lantern relations and rational blowdowns ', Proc. Amer. Math. Soc. 138 (2010) 1131-1142… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(117 citation statements)
references
References 13 publications
1
116
0
Order By: Relevance
“…Recall that the Floer homology group y HF pLpq, rq, sq in any spin c structure s is 1-dimensional over F, and lies in a grading denoted dpLpq, rq, sq P Q. These grading levels were computed recursively by Ozsváth and Szabó in [27,Proposition 4.8]; in our orientation convention their formula reads (10) dpLpq, rq, iq " 1 4qr`q r´p2i`1´q´rq 2˘´d pLpr, qq, iq.…”
Section: 2mentioning
confidence: 99%
“…Recall that the Floer homology group y HF pLpq, rq, sq in any spin c structure s is 1-dimensional over F, and lies in a grading denoted dpLpq, rq, sq P Q. These grading levels were computed recursively by Ozsváth and Szabó in [27,Proposition 4.8]; in our orientation convention their formula reads (10) dpLpq, rq, iq " 1 4qr`q r´p2i`1´q´rq 2˘´d pLpr, qq, iq.…”
Section: 2mentioning
confidence: 99%
“…Theorem 17 ([14], [12] (p = 2), [13] (p ≥ 3)). Let ̺, ̺ ′ be positive relators of Γ g , and let X ̺ , X ̺ ′ be the corresponding Lefschetz fibrations over S 2 , respectively.…”
Section: Rational Blowdownmentioning
confidence: 99%
“…Recently there has been much interest in trying to understand the topological interpretation of various relations in the mapping class group. A particularly well understood case is the daisy relation, which corresponds to the symplectic operation of rational blowdown [12,13]. Another interesting problem, which is still open, is whether any Lefschetz fibration over S 2 admits a section (see for example [36]).…”
Section: Introductionmentioning
confidence: 99%
“…The referees have suggested that Endo's idea may be extended in an inductive manner to give similar examples with base and fibre of genus g, for any g ≥ 3. We should use the "daisy chain relation" of [9], which is also the "generalized lantern relation" of [2], and is an iteration of the lantern relation.…”
Section: Bundles With Hyperbolic Fibrementioning
confidence: 99%